Design and experiment of automatic transplanting device for potted tomato seedlings. (February 2019) - Xin, Jin; Kaixuan, Zhao; Jiangtao, Ji; Hao, Ma; Jing, Pang; Zhaomei, Qiu
In this study, an automatic machine for transplanting potted tomato seedlings was designed, based on the analysis of physical characteristics of the main varieties of tomato seedlings. The machine is composed of a horizontal and vertical seedling supply mechanism, a picking mechanism composed with a gear-rod component, a planting part featured with an eccentric-disk parallelogram duckbilled mechanism, and a control system. The control system included position sensors, stepper motor, variable-frequency motor and program controller. The force condition for successful picking potted tomato seedlings was studied by analyzing the force and motion during the taking procedure with the use of analytical graphic method. Combined with the parameters of physical characteristics of tomato seedlings, the key parameters of the machine was determined, which included L 1  = 105 mm as the distance between the point of the gripper needles and the center of rotation, L 0  = 18 mm as the initial opening distance between the two gripper needles, and s  = 40 mm as the distance between the two gripper needles when they were at the upper hinge point of the clamping hands. The key structure and the parameters of the seedlings-taking part were determined by theoretical calculation according to the position of the seedling during taking and dropping procedure, and the requirement of the motion. The machine was tested by using the potted tomato seedlings. The result showed that the seedling picking rate was 92.35%–86.61%, and the leakage rate was 12.57%–18.03%, when the transplanting speed was between 60 and 90 seedlings per minute. The result demonstrated that the machine was feasible to transplant the potted tomato seedlings efficiently.